(untitled) (Fiep Bulletin - online, 2011)
Dyslexia is presented as a phenomenon that deserves the attention of researchers in education, especially because it can significantly impair the process of development of children in school. It is noteworthy that about 10 to 15% of the Brazilian population has dyslexia, is considered the highest incidence of difficulty in the classroom. Then, noted the need to conduct a study to examine the psychomotor profile, as well as the difficulties of written language and reading in children with dyslexia. Participants were three children with dyslexia with chronological age of 11 years, it is emphasized that the diagnoses of the children were performed by a qualified professional to do so. The methodological procedures used to Motor Development Scale (EDM) to detect the motor difficulties of dyslexic children and also held Survey of Reading and Writing Skills Test and the words and pseudo words (TCPP) to identify possible difficulties that affect the the teaching-learning of dyslexic children. The results that all children presented late in the body scheme, the spatial and temporal organization in Motor Development Scale. In the survey of Reading and Writing children had an alphabet, ie, already understand the whole system of writing, yet have misspellings, exchanges of letters and syllables reversals, characteristics of the problem. And Competence Test words and pseudo words in the results highlighted that all children also showed difficulties in pseudo homophones which suggests difficulty in lexical processing and indicates a restricted repertoire of vocabulary and, therefore, difficulties in storing the correct writing of words and their spelling rules. Evaluations were performed and the results obtained shows the need for action in the motor aspects of lag, as well as educational, since it is understood that these aspects baseline for the process of teaching and learning to occur properly.